Comparison of PGSE and STEAM DTI acquisitions with varying diffusion times for probing anisotropic structures in human kidneys. Issue 3 (18th February 2020) - Stabinska, Julia; Ljimani, Alexandra; Frenken, Miriam; Feiweier, Thorsten; Lanzman, Rotem Shlomo; Wittsack, Hans‐Jörg
Abstract : Purpose: To evaluate the sensitivity of stimulated‐echo acquisition mode (STEAM) and pulsed‐gradient spin‐echo (PGSE) diffusion tensor imaging (DTI) acquisitions with different diffusion times for measuring renal tissue anisotropy. Methods: Twelve healthy volunteers underwent an MRI examination at a 3T scanner including STEAM and PGSE DTI with variable diffusion times Δ (20.3, 37 and 125 ms). Three volunteers were scanned twice to test the reproducibility for repeated examinations. Diffusion parameters fractional anisotropy (FA) and apparent diffusion coefficient (ADC) in the automatically segmented cortical and medullary regions of interests in both kidneys were calculated and averaged over all subjects for further analysis. Moreover, 5‐grade qualitative evaluation of the FA and ADC maps from each sequence was conducted by two experienced radiologists in a consensus. Results: The cortex‐medulla difference in the STEAM sequence was significantly higher than that in PGSE with short ∆ = 20.3 ms ( P  < 0.001) and in PGSE with intermediate ∆ = 37 ms ( P  < 0.05) diffusion times. Reproducibility of the FA/ADC measurements was very good and comparable for all acquisition modes investigated. For the FA maps, the PGSE sequence with intermediate diffusion time scored highest in the subjective visual assessment of radiologists. Conclusion: The delineation of anisotropy in renal tissue is depending on the used diffusion time of the DTI sequence. A PGSE acquisition at a diffusion time of about 37 ms provides reproducible results with optimal corticomedullary contrast in FA and ADC maps and good image quality.